Preparation method and application of copper-phosphotungsten oxygen cluster catalyst

The ligand-modified copper-phosphorus tungsten oxide cluster catalyst catalyzed the conversion of 2-mercaptobenzothiazole to MBTS under photocatalytic conditions, solving the problems of high energy consumption and waste liquid pollution of traditional MBTS synthesis methods, and achieving efficient and selective green synthesis.

CN119565674APending Publication Date: 2025-03-07LIAOCHENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822224.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional MBTS synthesis methods have problems such as high energy consumption, waste liquid pollution and catalyst non-circulation, making it difficult to achieve economical, efficient and environmentally friendly green synthesis.

Method used

A ligand-modified copper-phosphorus tungsten oxide cluster catalyst was designed, prepared by coordination self-assembly under hydrothermal conditions, and applied to catalyze the conversion of 2-mercaptobenzothiazole to MBTS under photocatalytic conditions.

Benefits of technology

High-efficiency catalysis was achieved under visible light, the conversion rate of 2-mercaptobenzothiazole reached 81%, and the selectivity of MBTS was as high as 99%, while reducing energy consumption and waste liquid generation, achieving green and simple synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565674A_ABST
    Figure CN119565674A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of catalyst materials, in particular to a preparation method and application of a 4-(pyridine-2-yl)-6-(4-(pyridine-4-yl) phenyl) pyrimidine-2-amine copper-phosphotungsten oxygen cluster catalyst. The method comprises the following steps: sequentially mixing copper salt, phosphotungstic acid, 4-(pyridine-2-yl)-6-(4-(pyridine-4-yl) phenyl) pyrimidine-2-amine and deionized water in a container according to a certain proportion, putting the mixture into a polytetrafluoroethylene reaction kettle, reacting for a period of time at a certain temperature, gradually cooling, filtering, washing and drying to obtain the copper-phosphotungstic acid. The green crystal 4-(pyridine-2-yl)-6-(4-(pyridine-4-yl) phenyl) pyrimidine-2-amine copper-phosphotungstic oxygen cluster catalyst is obtained through a one-pot method. The catalyst can be applied to a reaction for synthesizing a rubber accelerator through photocatalytic coupling of 2-mercaptobenzothiazole. The method has the advantages of high reaction speed, simple reaction process, high purity of the obtained product, simple post-treatment and the like. And the catalyst has a clear molecular structure and is beneficial to research on a catalytic reaction mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst material preparation, and relates to a preparation technology of 4-(pyridine-2-yl)-6-(4-(pyridine-4-yl)phenyl)pyrimidine-2-amine copper-phosphorus tungsten oxygen cluster catalyst. Technical Background

[0002] 2,2'-Dibenzothiazole disulfide (MBTS) is widely used as a rubber vulcanization accelerator in industry. It can accelerate the vulcanization process, shorten the vulcanization time, and thus improve production efficiency; it can also improve the physical properties of the vulcanized rubber, such as tensile strength, elasticity, resilience and wear resistance, and enhance chemical stability; it can also optimize the operability of the vulcanization system, improve the vulcanization start-up characteristics, and improve scorch safety. In China, about 80,000 tons of MBTS are used for rubber accelerators every year. In recent years, with the rapid development of the automobile and tire industries, the demand for rubber additives has increased year by year, which has also brought a larger market for MBTS.

[0003] MBTS is a traditional chemical. The earliest recorded synthesis process can be traced back to the 1980s. So far, there are some patented synthesis methods. Its synthesis is generally based on 2-mercaptobenzothiazole in the presence of strong oxidants such as NaClO or NaNO. 2 The reaction is completed under mild conditions (Ind. Eng. Chem. Res. 2021, 60, 10094; Green Chem., 2017, 19, 2491), which consumes a lot of energy and produces high-salt wastewater and nitrogen oxides, making the post-treatment cost very high. Therefore, finding an economical, efficient, mild reaction condition, environmentally friendly and easy to recycle catalyst is still a very important issue at present. Efficient construction of SS bonds under mild conditions is also our work goal, and the key lies in the selection of catalysts.

[0004] Photocatalysis is a chemical reaction process that uses light energy to transform substances. Under the combined action of light and catalysts, substances undergo chemical reactions (Appl. Catal. B: Environ., 2023, 323, 122134. Chem. Soc. Rev., 2018, 47,8134). It uses light energy as a driving force and is a green and environmentally friendly technology that avoids pollution and greenhouse gas emissions caused by traditional energy. In addition, the photocatalytic reaction conditions are relatively mild and can generally be carried out at room temperature and pressure, reducing the dependence on complex and harsh reaction conditions. Therefore, the research on photocatalytic synthetic rubber additives is of great significance.

[0005] According to the concept of green synthesis, it is very necessary to design a catalyst for the green and simple synthesis of MBTS under mild conditions. To this end, we designed and synthesized a ligand-modified copper-phosphotungsten oxygen cluster catalyst that can efficiently catalyze the synthesis of MBTS under visible light.

[0006] Through searching, no published patent documents related to the present invention application have been found. Summary of the invention

[0007] The purpose of this invention is to catalyze the conversion of 2-mercaptobenzothiazole to MBTS. The traditional thermochemical synthesis strategy has problems such as high reaction energy consumption, serious environmental pollution of waste liquid, and non-recyclable catalysts. We provide a preparation method of a ligand-modified copper-phosphorus tungsten oxygen cluster catalyst, in order to achieve the construction of SS bonds in the field of photocatalysis and achieve the goal of efficiently synthesizing MBTS under mild, green and simple conditions.

[0008] The design ideas of the present invention are as follows:

[0009] 1. A ligand-modified copper-phosphotungsten oxygen cluster catalyst was synthesized in one pot by coordination self-assembly under hydrothermal conditions using ligand 4-(pyridin-2-yl)-6-(4-(pyridin-4-yl)phenyl)pyrimidine-2-amine (ligand L), copper salt and phosphotungstic acid;

[0010] 2. A ligand-modified copper-phosphotungsten oxygen cluster catalyst with a well-defined structure was used to convert 2-mercaptobenzothiazole into MBTS under photocatalytic molecular oxygen conditions.

[0011] The crystal structure information of this type of catalyst was obtained by the following method:

[0012] The crystals of the ionic multi-site single-component catalyst were synthesized by conventional hydrothermal method. The specific experimental method is described as follows:

[0013] (0.27 ~ 0.54 mmol) copper salt, (0.10 ~ 0.20 mmol) ligand L, (0.10 ~ 0.20 mmol) phosphotungstic acid hydrate, were added to a 25 mL beaker, and then 8 ~ 10 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.12 ~ 1.94 by adding 1 M dilute sodium hydroxide dropwise. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and maintained at 140 ~ 160 ° C for 72h ~ 96h, and then gradually cooled to 25 ° C for 14 ~ 24h, and finally green crystals [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2O, wash the obtained crystals and place them in the air to dry, with a yield of about 30-66%.

[0014] The product was characterized by single crystal X-ray diffraction, powder X-ray diffraction and infrared IR spectroscopy to obtain accurate information about the crystal structure. The specific results are as follows:

[0015] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 The structure of O is Figure 1 The structural unit of the compound contains two [Cu(L)(OH)] + , a classic keggin structure (HPW 12 O 40 ) 2- and two free water molecules. 12 O 40 ) 2- Connected two [Cu(L)(OH)] + Monomer, can be regarded as di-coordinated form. [Cu(L)(OH)] + The copper atom is penta-coordinated, with two N atoms coming from the two connected rings of the ligand L and two O atoms coming from (HPW 12 O 40 ) 2- The terminal oxygen atom of the HPW 12 O 40 ) 2- They are connected by O-Cu-O to form a two-dimensional network shape.

[0016] This invention is mainly a catalyst for the photocatalytic synthesis of MBTS, which has been applied to the photocatalytic conversion of 2-mercaptobenzothiazole into MBTS. This type of catalyst can achieve a conversion rate of 81% for 2-mercaptobenzothiazole and a selectivity of 99% for MBTS after 24 hours of reaction under 20W light irradiation and a wavelength of 470nm. The preparation method of this type of catalyst has a simple reaction process.

[0017] The present invention has the following beneficial effects:

[0018] 1. The preparation method is simple and the catalysts have a clear molecular structure, which is conducive to studying the mechanism of catalytic reactions.

[0019] 2. The catalyst can realize the conversion of 2-mercaptobenzothiazole to MBTS under visible light. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1. Compound [[Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Schematic diagram of the crystal structure of O;

[0021] Figure 2 . Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 RXRD characterization of O. DETAILED DESCRIPTION

[0022] In order to demonstrate the essential features and significant improvements of the present invention, the following examples are used to further illustrate the implementation methods and effects.

[0023] Embodiment 1:

[0024] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0025] 0.27 mmol copper nitrate, 0.10 mmol ligand L, and 0.10 mmol phosphotungstic acid hydrate were added to a 25 mL beaker in sequence, and 10 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.12 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 160 °C for 3 days, and then gradually cooled to 25 °C for 14 h to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 50%.

[0026] Embodiment 2:

[0027] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0028] 0.32 mmol copper nitrate, 0.12 mmol ligand L, and 0.12 mmol phosphotungstic acid hydrate were added to a 25 mL beaker, and then 8 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.74 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 140 °C for 90 hours, and then gradually cooled to 25 °C for 18 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 37%.

[0029] Embodiment 3:

[0030] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0031] 0.37 mmol of copper chloride, 0.14 mmol of ligand L, and 0.14 mmol of phosphotungstic acid hydrate were added to a 25 mL beaker in sequence, and then 10 mL of distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.24 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 140 °C for 96 hours, and then gradually cooled to 25 °C for 14 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 30%.

[0032] Embodiment 4:

[0033] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0034] 0.27 mmol of copper acetate, 0.10 mmol of ligand L, and 0.10 mmol of phosphotungstic acid hydrate were added to a 25 mL beaker, and 10 mL of distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.34 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and maintained at 150 °C for 96 hours, and then gradually cooled to 25 °C for 14 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 32%.

[0035] Embodiment 5:

[0036] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0037] 0.54 mmol of copper acetate, 0.20 mmol of ligand L, and 0.20 mmol of phosphotungstic acid hydrate were added to a 25 mL beaker, and 10 mL of distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.44 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 160 °C for 90 hours, and then gradually cooled to 25 °C for 14 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 38%.

[0038] Embodiment 6:

[0039] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0040] 0.54 mmol copper nitrate, 0.20 mmol ligand L, and 0.20 mmol phosphotungstic acid hydrate were added to a 25 mL beaker in sequence, and 10 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.54 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 140 °C for 72 hours, and then gradually cooled to 25 °C for 22 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 43%.

[0041] Embodiment 7:

[0042] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0043] 0.43 mmol copper nitrate, 0.16 mmol ligand L, and 0.16 mmol phosphotungstic acid hydrate were added to a 25 mL beaker, and 10 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.64 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 150 °C for 76 hours, and then gradually cooled to 25 °C for 14 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 39%.

[0044] Embodiment 8:

[0045] Compound [Cu(L)(OH)] 2 (HPW 12 O40 )·2H 2 Preparation of O

[0046] 0.27 mmol copper nitrate, 0.10 mmol ligand L, and 0.10 mmol phosphotungstic acid hydrate were added to a 25 mL beaker, and 10 mL distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.74 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 160 °C for 80 hours, and then gradually cooled to 25 °C for 24 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 66%.

[0047] Embodiment 9:

[0048] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0049] 0.54 mmol of copper chloride, 0.20 mmol of ligand L, and 0.20 mmol of phosphotungstic acid hydrate were added to a 25 mL beaker, and 10 mL of distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.84 by adding 1 M dilute sodium hydroxide. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 160 °C for 80 hours, and then gradually cooled to 25 °C for 16 hours to finally obtain green crystals. The obtained crystals were washed and air-dried, with a yield of 45%.

[0050] Embodiment 10:

[0051] Compound [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 Preparation of O

[0052] 0.27 mmol of copper chloride, 0.10 mmol of ligand L, and 0.10 mmol of phosphotungstic acid hydrate were added to a 25 mL beaker in sequence, and then 10 mL of distilled water was added to mix. After the mixture was stirred for 1 hour, the pH value of the solution was adjusted to 1.94 by adding 1 M dilute sodium hydroxide dropwise. The resulting mixture was transferred to a polytetrafluoroethylene-lined reactor and kept at 160 °C for 72 hours, and then gradually cooled to 25 °C for 20 hours to finally obtain green crystals. The obtained crystals were washed and placed in the air to dry, with a yield of 50%.

[0053] As shown in Table 1, the compound [Cu(L)(H2 O)] 2 (PW 12 O 40 )·2H 2 Crystallographic data of O

[0054] .

[0055] Embodiment 11:

[0056] Application of a ligand-modified copper-phosphotungsten oxide cluster catalyst in the conversion of 2-mercaptobenzothiazole to MBTS.

[0057] example:

[0058] 1.00 mmol of 2-mercaptobenzothiazole was placed in a 20 mL pressurized photocatalyst, and 0.05 mmol of catalyst was added. The oxygen pressure was controlled to 2.0 MPa. Under 20W 470nm light irradiation, after 24 hours of reaction, 81% of the 2-mercaptobenzothiazole in the reaction solution was converted into the product, and the selectivity of MBTS reached 99%.

[0059] As shown below, the catalyst [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 The results of the photocatalytic conversion of 2-mercaptobenzothiazole to MBTS by O are as follows:

[0060]

[0061] The above results show that [Cu(L)(OH)] 2 (HPW 12 O 40 )·2H 2 O exhibits efficient catalytic activity in the synthesis of MBTS. Under visible light conditions, it can effectively catalyze the conversion of 2-mercaptobenzothiazole to form MBTS compounds, with a conversion rate of 81% and a selectivity of 99% within 24 hours. The above results show that this ligand-modified copper-phosphorus tungsten oxygen cluster catalyst exhibits efficient selectivity for the generation of MBTS and does not produce excess waste liquid. It highlights the ability of photocatalytic green synthesis and solves the scientific problems of high energy consumption and high pollution in the MBTS synthesis process.

[0062] Of course, the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the specific implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above examples. It is impossible to give detailed examples of all implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a copper-phosphotungsten oxide cluster catalyst, comprising the steps of: sequentially adding copper salt, 4-(pyridin-2-yl)-6-(4-(pyridin-4-yl)phenyl)pyrimidine-2-amine, phosphotungstic acid and water into a container, adjusting the pH value of the solution by dropping dilute sodium hydroxide, stirring for 2 h, reacting at a certain temperature for a certain time, and finally obtaining green crystals [Cu(L)(OH)]2(HPW 12 O 40 )·2H2O, wash the obtained crystals and then air dry them.

2. The method for preparing a copper-phosphorus tungsten oxide cluster catalyst according to claim 1, characterized in that: The reaction solvent is water, the ratio of the reaction raw materials is copper salt: 4-(pyridin-2-yl)-6-(4-(pyridin-4-yl)phenyl)pyrimidine-2-amine: phosphotungstic acid, the molar ratio is 0.27 ~ 0.54: 0.10 ~ 0.20: 0.10 ~ 0.20, the solution pH is 1.12 ~ 1.94, the reaction temperature is 140 ~ 160 ° C; the reaction time is 72h ~ 96h.

3. Use of the copper-phosphorus tungsten oxygen cluster catalyst obtained by the preparation method according to any one of claims 1 to 2 in catalyzing the reaction of 2-mercaptobenzothiazole to construct SS bonds to generate rubber accelerator 2,2'-dibenzothiazole disulfide.